Pengaruh (Attitude, Attention, dan Action) Karyawan terhadap Loyalitas Nasabah pada Pt. Bank Sumut Kantor Cabang Syariah Medan Karya - Angelly Pratiwi; Nurbaiti, Nurbaiti; Muhammad Ikhsan Harahap (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
The purpose of this research is to determine the influence of employee roles (Attitude, Attention and Action) on achieving customer loyalty at PT. North Sumatra Bank Medan Karya Sharia Branch Office. The influence of employee roles (Attitude, Attention and Action) has a positive effect on achieving customer loyalty at PT. North Sumatra Bank Medan Karya Sharia Branch Office. Quantitative research is research that uses data in the form of numbers. This shows that (Attitude, Attention and Action) have a positive effect on achieving customer loyalty at PT. North Sumatra Bank Medan Karya Sharia Branch Office. (Attitude, Attention and Action) has an influence of 98.4% on achieving customer loyalty at PT. North Sumatra Bank Medan Karya Sharia Branch Office. Meanwhile, 1.6% is influenced by other factors not included in the regression model. The significance of the variables (Attitude, Attention and Action) is 0.000, which is less than the significant value level used, namely 0.05. The attitude variable is 26.116, the value is above the research value, namely 1.984. The Attention variable is 7.708, the value is above the research value, namely 1.984. The Action variable is 8.256, the value is above the research value, namely 1.984.